COMMUNITY BEHAVIOR TOWARDS DENGUE INCIDENTS IN PASIR VILLAGE, CENTRAL TAPANULI REGENCY IN 2021 - Della Winda Gultom; Tinawati Nainggolan; Jonni Silaban (Science Midwifery, 2022)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus and transmitted by Aedes aegypti and Aedes albopictus mosquitoes. Increased DHF incidences caused by the unclean lifestyle of people. This study was an analytical study with a cross-sectional approach. The aim was to determine the relationship between individual characteristics, behavior, and environment on the incidence of DHF. Data were collected by interview and observation using a questionnaire and observation sheet. Data analyzed by univariate and bivariate methods with a chisquare analysis test. The number of samples was 107 people with the sampling technique used was simple random sampling. The results showed that 15.9% of the community had dengue fever in the last six months. There were 4 variables that have a relationship to the incidence of DHF, namely age (p-value = 0,000), gender (pvalue = 0.017, OR = 4.146), knowledge (p-value = 0.034, OR = 5.231), actions (p-value = 0.045, OR = 3.740), while education (pvalue = 0.086), work (p-value = 0.748), attitude (p-value = 0.078), the existence of larvae (p-value = 0.716) does not have a relationship to the incidence of DHF and 1 variable cannot be connected namely the existence of a water reservoir because 100% have a water reservoir and 1 variable only looks at the description of DHF events by season.